Severe declines in numbers of male American Common Eiders Somateria mollissima dresseri during spring counts over the past two decades in the southwestern Bay of Fundy, Canada - Gutowsky, Sarah E.; Mallory, Mark L.; McLellan, Nic R.; Robertson, Gregory J.; Connor, Kevin; Gilliland, Scott G. (Wildfowl, 2024)
The southwestern Bay of Fundy in New Brunswick, Canada, has traditionally provided important habitat year-round for American Common Eider Somateria mollissima dresseri. Numerous anthropogenic stressors from industry and climate change are thought to be having a negative impact on the abundance of dresseri eiders wintering and breeding in this region. We analysed trends in the number of eiders breeding in the Bay of Fundy, recorded during dedicated aerial surveys made to count males attending colonies in spring, flown nearly biannually since 1991. A combination of negative binomial generalized additive models (GAMs) and generalized linear models (GLMs) were used to assess changes in eider numbers over the past 30 years across the entire study region and at the scale of smaller spatial sub-units. We found that the number of eiders breeding in the Bay of Fundy began to decline steeply around the year 2000 in all surveyed areas with an overall regional trend of λ = 0.91 (95% confidence interval = 0.89, 0.92), amounting to a loss of nearly 10% per year over the past two decades. The largest concentrations of nesting eiders continue to be associated with the Grand Manan Archipelago, although numbers have declined there as well. Comparing two years with equal and extensive spatial coverage of surveyed areas, the total number of male eiders counted in the spring in the Bay of Fundy dropped from 8,890 in 1998 to 2,562 in 2017. Altogether, these findings corroborate other evidence that eiders have been declining throughout the Gulf of Maine ecosystem at an alarming rate over the past 20 years, and that distributional shifts are likely occurring across the subspecies’ range.